2020
DOI: 10.7554/elife.56086
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glia as a source of neural progenitors in adult zebrafish

Abstract: The presence and identity of neural progenitors in the enteric nervous system (ENS) of vertebrates is a matter of intense debate. Here, we demonstrate that the non-neuronal ENS cell compartment of teleosts shares molecular and morphological characteristics with mammalian enteric glia but cannot be identified by the expression of canonical glial markers. However, unlike their mammalian counterparts, which are generally quiescent and do not undergo neuronal differentiation during homeostasis, we show that a rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 96 publications
6
66
1
Order By: Relevance
“…In light of the substantial mutational load described in BE tissues 46 , the chronic inflammatory environment of the pL2 mouse model combined with increased Notch signaling may thus suffice to induce oncogenic growth from Dclk1-positive tuft cells. Lastly, Dclk1 is also expressed in cells of the enteric nervous system (ENS) 21 , 47 , and modulations of Notch signaling in cells of the ENS may result in an altered glial and neuronal differentiation 48 , 49 and contribute to the epithelial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the substantial mutational load described in BE tissues 46 , the chronic inflammatory environment of the pL2 mouse model combined with increased Notch signaling may thus suffice to induce oncogenic growth from Dclk1-positive tuft cells. Lastly, Dclk1 is also expressed in cells of the enteric nervous system (ENS) 21 , 47 , and modulations of Notch signaling in cells of the ENS may result in an altered glial and neuronal differentiation 48 , 49 and contribute to the epithelial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also showed zebrafish Glial fibrillary acidic protein (Gfap) immunohistochemistry staining where, enteric glia processes largely form an inner layer separating neuronal axons from the intestinal epithelium (Baker et al, 2019 ). However, another report states that the observed Gfap staining likely represents cross-reactivity, as it persisted in ret mutant larvae lacking an ENS (McCallum et al, 2020 ). Moreover, they show that zebrafish enteric glia do not seem to (highly) express the canonical “glial markers” such as, the fatty acid binding protein 7 (Fabp7) and the S100 calcium-binding protein B (s100β).…”
Section: Zebrafish As a Model Organism To Study The Ensmentioning
confidence: 99%
“…They also show that, zebrafish enteric glia resemble mammalian enteric glia based on their ultrastructural and general morphology, gene expression and location. The her4.3 + cells were defined as neural crest derived, post-migratory cells that retain proliferative and neurogenic potential throughout life (McCallum et al, 2020 ). An independent study, also reported the presence of neurogenic precursors in adult zebrafish, that lack expression of the canonical “glial marker” Gfap (El-Nachef and Bronner, 2020 ).…”
Section: Zebrafish As a Model Organism To Study The Ensmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, ZEB2-co-controlled astrocyte activation and reactive gliosis, including in a context of multicellular responses (including microglia; [ 188 ]) to nervous system damage and disease, is an exciting new ZEB2 research line to explore in mouse and zebrafish models for (repetitive) injuries and pathologies of the brain [ 189 ], spinal cord [ 190 ], retina [ 191 ] and ENS [ 192 , 193 ], and perhaps, more speculative, also in blood vessel disease caused by endothelial dysfunction, e.g., in the brain and in neuroretinal degeneration [ 194 ].…”
Section: Zeb2 In the Development Of Nervous Systems In Vertebratesmentioning
confidence: 99%